Uncovering of Potential Fraud in the Preparation of Village Planning and Budgeting Documents in Madura - Tarjo, Tarjo; Faizah, Yustin Nur; Toyyib, Moh.; Sakti, Eklamsia; Pramudita, Heindrika Eka (Jurnal Ilmiah Akuntansi dan Bisnis, 2021)
This study determines the planning and budgeting of documents in the gray village. Researchers empirically evaluate and demonstrate how the actual practice of village government was conducted. This study uses a qualitative approach to the case study method to analyze the data, which was drawn from unstructured interviews, observations, and documentation. The findings reveal how opportunities for fraud can be due to a lack of understanding of functions, duties, and responsibilities and how they also affect budget preparation. This is due to the pressure in completing planning and budgeting documents that affect uninformed village chairmen and chiefs who are signing documents. Another finding is that there are typically two village secretaries who act as financial coordinators for one village government.